The impact of Public Service Motivation on Organizational Commitment in the Thai Bureaucracy - Thongbai, Pongsun (2019)
Several articles of public administration pointed out that Public Service Motivation (PSM) has a positive consequence on organizational commitment (OC). Many of them considered PSM and OC as the overall variable instead of dividing four dimensions of PSM proposed by Perry (1996) and three components of OC introduced by Meyer & Allen (1991) to be every single variable, and there was still a lack of research in this field in the Thai public sector. Therefore, the objective of this study is to determine how PSM has an impact on OC in the Thai bureaucracy by discussing their every possible dimension. To answer this question, an empirical online-survey was conducted, with 131 Thai police inquiry officials serving in the metropolitan bureau of Bangkok were participated. The finding suggests that all dimensions of PSM have a moderately positive impact on Affective commitment in the Thai public organizations, and two of them are also positively related to Normative commitment. However, their abilities to predict OC are various. Unexpectedly, the result indicates that PSM is not relevant to Continuance commitment. Further research is required to identify why this consequence is not consistent with the previous studies.